2015
DOI: 10.1002/eji.201545487
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐regulation between cytokine and microRNA pathways in T cells

Abstract: microRNA (miRNA) mediated regulation of protein expression has emerged as an important mechanism in T-cell physiology, from development and survival to activation, proliferation, and differentiation. One of the major classes of proteins involved in these processes are cytokines, which are both key input signals and major products of T-cell function. Here, we summarize the current data on the molecular cross-talk between cytokines and miRNAs: how cytokines regulate miRNA expression, and how specific miRNAs cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 108 publications
(246 reference statements)
3
34
0
Order By: Relevance
“…Another recent in vivo study, performed on mir-155 and mir-146a knockout mice, has demonstrated that miRNA entrapped in exosomes is able to modulate the immune response and repress gene expression in target organs (Alexander et al, 2015). The miR-146a is known to possess strong anti-inflammatory activity, whereas mir-155 is, on the contrary, involved in pro-inflammatory responses (Turner et al, 2011;Amado et al, 2015). Intraperitoneal injection of 10 9 wild type exosomes into mir-155 knockout mice, and subsequent stimulation of the immune system by lipopolysaccharide injections induced strong pro-inflammatory cytokine TNF-alpha up-regulation in the blood plasma.…”
Section: сEll-cell Communication Via Circulating Micrornasmentioning
confidence: 97%
“…Another recent in vivo study, performed on mir-155 and mir-146a knockout mice, has demonstrated that miRNA entrapped in exosomes is able to modulate the immune response and repress gene expression in target organs (Alexander et al, 2015). The miR-146a is known to possess strong anti-inflammatory activity, whereas mir-155 is, on the contrary, involved in pro-inflammatory responses (Turner et al, 2011;Amado et al, 2015). Intraperitoneal injection of 10 9 wild type exosomes into mir-155 knockout mice, and subsequent stimulation of the immune system by lipopolysaccharide injections induced strong pro-inflammatory cytokine TNF-alpha up-regulation in the blood plasma.…”
Section: сEll-cell Communication Via Circulating Micrornasmentioning
confidence: 97%
“…miRNAs can be involved in this regulation system, especially at transcriptional and processing levels. miRNAs can regulate cytokine production, and cytokines can modulate miRNA levels …”
Section: Discussionmentioning
confidence: 99%
“…miR‐29c‐3p has been described as one of the regulators of retinal neurogenesis, since its targets are retinal regulatory genes, an integral part of CNS. Thus, miR‐29c‐3p may play a similar role during neurogenesis in other parts of the brain …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…112 Interactions between cytokines and miRNA pathways regulate T-cell functions. 113 In addition, miRNA induced in antigen-stimulated T cells can regulate post-transcriptional expression of various cellular proteins including cytokines by targeting mRNAs for either degradation or translational inhibition. In fact, naive, effector, and memory functional states of T cells were shown to have characteristic miRNA profiles.…”
Section: B Non-coding Rnamentioning
confidence: 99%